Impact of right ventricular dyssynchrony on prognosis of patients with idiopathic pulmonary arterial hypertension. (October 2019) - Cheng, Xiao-Ling; Liu, Bing-Yang; Wu, Wei-Chun; Li, Wen; Huang, Li; Yang, Tao; Liu, Zhi-Hong; Wang, Hao; He, Jian-Guo; Xiong, Chang-Ming
Idiopathic pulmonary arterial hypertension is a progressive disease with high mortality with an increasing burden of right ventricular. Right ventricular dyssynchrony was observed in idiopathic pulmonary arterial hypertension, but the association with mortality is unclear. This study aimed to investigate the impact of right ventricular dyssynchrony on the survival of idiopathic pulmonary arterial hypertension. A total of 116 patients with idiopathic pulmonary arterial hypertension were enrolled in this study. All these patients underwent comprehensive clinical evaluation. Right ventricular dyssynchrony was assessed by two-dimensional speckle-tracking echocardiography. The time to peak strain (Tpeak ) of right ventricular segments were obtained. Right ventricular dyssynchrony was quantified by the standard deviation of the heart rate-corrected Tpeak of right ventricular four segments. All patients were followed up and the primary endpoint was all cause of death. Results found patients with significant right ventricular dyssynchrony present with advanced World Health Organization functional class, worse hemodynamic status and right ventricular function. Right ventricular dyssynchrony was an independent predictive factor for the survival of idiopathic pulmonary arterial hypertension. Kaplan–Meier survival curves showed patients with right ventricular dyssynchrony had worse prognosis. In conclusion, right ventricular dyssynchrony analyzed by speckle-tracking echocardiography provided added value to hemodynamic and echocardiographic parameters in evaluating the survival of patients with idiopathic pulmonary arterial hypertension.